From anger to apathy : the British experience since 1975 / Mark Garnett. - Garnett, Mark, 1963- (Vintage, 2008)
In 1975, Britons spent much of their time complaining - and for good reasons. In this groundbreaking book, Mark Garnett charts the changes in British politics, society and culture since 1975.